Prostate cancer classification using 3D deep learning and ultrasound video clips: a multicenter study - Lou, Wenjie; Chen, Peizhe; Wu, Chengyi; Liu, Qinghua; Zhou, Lingyan; Zhang, Maoliang; Tu, Jing; Hu, Zhengbiao; Lv, Cheng; Yang, Jie; Qi, Xiaoyang; Sun, Xingbo; et al. (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of deep-learning models using transrectal ultrasound (TRUS) video clips in predicting prostate cancer.MethodsWe manually segmented TRUS video clips from consecutive men who underwent examination with EsaoteMyLab™ Class C ultrasonic diagnostic machines between January 2021 and October 2022. The deep learning-inflated 3D ConvNet (I3D) model was internally validated using split-sample validation on the development set through cross-validation. The final performance was evaluated on two external test sets using geographic validation. We compared the results obtained from a ResNet 50 model, four ML models, and the diagnosis provided by five senior sonologists.ResultsA total of 815 men (median age: 71 years; IQR: 67–77 years) were included. The development set comprised 552 men (median age: 71 years; IQR: 67–77 years), the internal test set included 93 men (median age: 71 years; IQR: 67–77 years), external test set 1 consisted of 96 men (median age: 70 years; IQR: 65–77 years), and external test set 2 had 74 men (median age: 72 years; IQR: 68–78 years). The I3D model achieved diagnostic classification AUCs greater than 0.86 in the internal test set as well as in the independent external test sets 1 and 2. Moreover, it demonstrated greater consistency in sensitivity, specificity, and accuracy compared to pathological diagnosis (kappa > 0.62, p < 0.05). It exhibited a statistically significant superior ability to classify and predict prostate cancer when compared to other AI models, and the diagnoses provided by sonologists (p<0.05).ConclusionThe I3D model, utilizing TRUS prostate video clips, proved to be valuable for classifying and predicting prostate cancer.